2022
DOI: 10.15255/kui.2021.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Toxicity on the Growth and Photosynthetic Pigment Contents of Salix purpurea in Mitrovica, Kosovo

Abstract: In Mitrovica, Kosovo, mining activity is threatening the environment and living organisms. The major sources of this pollution are the open tailing dumps in the city of Mitrovica, causing contamination of soil, air, and plants. This study determines heavy metal contamination levels in Salix purpurea leaf grown in the city of Mitrovica and its surrounding area, where the industrial plants and open tailing dumps of mineral processing are located. Furthermore, the photosynthetic activity of the plant was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Al-Rashedy and Al-Mtewti (2022) also reported that treating the soil with heavy elements led to a decline in the concentration of carbohydrates, one of the products of photosynthesis that depend on chlorophyll concentrations. Ferati et al (2022) noted that exposure to heavy metals affected the photosynthetic pigments in the plant leaves of Salix purpurea.…”
Section: Soilmentioning
confidence: 99%
“…Al-Rashedy and Al-Mtewti (2022) also reported that treating the soil with heavy elements led to a decline in the concentration of carbohydrates, one of the products of photosynthesis that depend on chlorophyll concentrations. Ferati et al (2022) noted that exposure to heavy metals affected the photosynthetic pigments in the plant leaves of Salix purpurea.…”
Section: Soilmentioning
confidence: 99%